THE EFFECT OF SOAKING TIME ON PEDADA FRUIT SKIN EXTRACT(Sonneratia caseolaris) TOWARD MICROBIOLOGY QUALITY OF NILE TILAPIA (Oreochromisniloticus) FILLET DURING COLD TEMPERATURE STORAGE (±50C) - Suryana Suryana; N Ira Sari; Syahrul Syahrul (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research was aimed to determine the effect of soaking time on pedada fruit skin extract(Sonneratia caseolaris) toward microbiology quality of nile tilapia (Oreochromisniloticus) fillet during cold temperature storage(±50C).The method used in this research was a Randomized Block Design (RBD) non factorial with 3 treatment levelsP0(without pedada fruit skin extract), P30(soaking on pedada fruit skin extract for 30 minutes), and P60(soaking on pedada fruit skin extract for 60 minutes) with a concentration 30% and soaking time in a cold temperature (±50C) for0, 7, 14 and 21 days. The tested parameters were microbiology analysis (total bacterial colony, Salmonella sp,Escherichia coli) and organoleptic analysis (appearance, odor, texture, and taste). The result indicatedthat the tilapia fillet was significantly affect to the microbiology and organoleptic quality, whereas the treatment with soaking on pedada fruit skin extract for 60 minutes and 21 days of storagewas the best treatmentwith total bacterial colony1.8 x 105colony/g, Salmonella sp (negative), Escherichia coli (negative), and organoleptic tested for appearance(6.4) with characteristic of flesh was white and attractive, odor(6.4) with a fresh and specific of nile tilapia smell, texture(6.4) elastic rather soft and compact, taste (6.0) rather tasty and specific fresh fish taste during 14 days of cold storage.Keywords:pedada fruit skin, tilapia fillet andduring storage